Role of Neonatal Biomarkers of Exposure to Psychoactive Substances to Identify Maternal Socio-Demographic Determinants - Pilar Jarque; Antonia Roca; Isabel Gomila; Emilia Marchei; Roberta Tittarelli; Miguel Ángel Elorza; Pilar Sanchís; Bernardino Barceló (Biology, 2021)
Background: The accurate assessment of fetal exposure to psychoactive substances provides the basis for appropriate clinical care of neonates. The objective of this study was to identify maternal socio-demographic profiles and risk factors for prenatal exposure to drugs of abuse by measuring biomarkers in neonatal matrices. Methods: A prospective, observational cohort study was completed. Biomarkers of fetal exposure were measured in meconium samples. The mothers were interviewed using a questionnaire. Univariate and multivariate logistic regression analyses were performed. Results: A total of 372 mothers were included, 49 (13.2%) testing positive for psychoactive substances use: 24 (49.0%) for cannabis, 11 (22.5%) for ethyl glucuronide, six (12.2%) for cocaine, and in eight (16.3%) more than one psychoactive substance. Mothers who consumed any psychoactive substance (29.7 ± 6.6 years) or cannabis (27.0 ± 5.7 years) were younger than non-users (32.8 ± 6.2 years, p < 0.05). Cocaine (50.0% vs. 96.9%, p < 0.05) and polydrug users (37.5% vs. 96.9%, p < 0.05) showed a lower levels of pregnancy care. Previous abortions were associated with the use of two or more psychoactive substances (87.5% vs. 37.8%, p < 0.05). Single-mother families (14.3% vs. 2.5%, p < 0.05) and mothers with primary level education (75.5% vs. 55.1%, p < 0.05) presented a higher consumption of psychoactive substances. Independent risk factors that are associated with prenatal exposure include: maternal age < 24 years (odds ratio: 2.56; 95% CI: 1.12–5.87), lack of pregnancy care (odds ratio: 7.27; 95%CI: 2.51–21.02), single-mother families (odds ratio: 4.98; 95%CI: 1.37–8.13), and active tobacco smoking (odds ratio: 8.13; 95%CI: 4.03–16.43). Conclusions: These results will allow us to develop several risk-based drug screening approaches to improve the early detection of exposed neonates.